2002
DOI: 10.1099/0022-1317-51-7-564
|View full text |Cite
|
Sign up to set email alerts
|

Transferable tetracycline resistance in Listeria monocytogenes from food in Italy

Abstract: Mechanisms of tetracycline resistance were investigated in two recent Listeria monocytogenes isolates from food, with L. innocua 52P tet r as a control. Tetracycline resistance was transferred conjugatively from all three strains to L. ivanovii and from one isolate and the control to Enterococcus faecalis. Molecular analysis demonstrated a chromosomal location for the tet determinant, which was identified as tetM in all cases. These studies are the first to show that L. monocytogenes from food could be a sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…In line with the conclusions of a recent Italian study reporting on the presence of transferable tet(M) genes in food isolates of L. monocytogenes (Pourshaban et al, 2002), our data indicate that this species could act as a reservoir of mobile tet genes along the human food chain. Previously, the transfer of tet(M) has also been demonstrated in the reverse direction from Enterococcus faecalis to Listeria sp.…”
Section: Molecular Detection and Characterization Of Resistance Genessupporting
confidence: 79%
“…In line with the conclusions of a recent Italian study reporting on the presence of transferable tet(M) genes in food isolates of L. monocytogenes (Pourshaban et al, 2002), our data indicate that this species could act as a reservoir of mobile tet genes along the human food chain. Previously, the transfer of tet(M) has also been demonstrated in the reverse direction from Enterococcus faecalis to Listeria sp.…”
Section: Molecular Detection and Characterization Of Resistance Genessupporting
confidence: 79%
“…Antibiotic resistance in L. monocytogenes can be acquired or transferred by genes from plasmids and transposons of other Gram-positive bacterial species such as Enterococcus spp., or mutational events in chromosomal genes (Charpentier, Gerbaud, Jacquet, Rocourt, & Courvalin, 1995;Harakeh et al, 2009;Pourshaban, Ferrini, Cannoni, Oliva, & Aureli, 2002). The newly acquired resistance will protect the bacteria from being disrupted during antibiotic treatment (Pesavento et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…is possible and can be due to acquisition of a replicon originating in enterococci-streptococci. It is known that microorganisms (bacteria) can either acquire, or transfer antibiotic resistance genes from plasmids and transposons of other bacterial species (including Enterococci spp) either in vitro or in vivo in the intestinal tract (29,28). This is very important for their pathogenicity as bacteria that acquire new resistance are not disrupted by antibiotics during therapy.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Studies with different bacterial pathogens showed that transfer of resistance was a common event (28). The developments in molecular biology enabled the genetic basis of this transfer, by extra chromosomal DNA (Rfactor or plasmids) to be explained (29). Bacteria have developed a wide range of mechanisms to avoid the action of antimicrobials, from antibiotic destroying enzymes to modifications of their own metabolic pathways.…”
Section: Discussion/conclusionmentioning
confidence: 99%